The Effect of Investment Constraints on Hedge Fund Investor Returns - Joenväärä, Juha; Kosowski, Robert; Tolonen, Pekka (Journal of Financial and Quantitative Analysis, 2019)
This paper examines the effect of real-world, investor-level investment constraints, including several that have not been studied before, on hedge fund performance and its persistence. Using a large consolidated database, we demonstrate that hedge fund performance persistence is significantly reduced when rebalancing rules reflect fund size restrictions and liquidity constraints but remains statistically significant at higher rebalancing frequencies. Hypothetical investor portfolios that incorporate additional minimum diversification constraints, minimum investment requirements, and focus on open funds suggest that the performance and its persistence documented in earlier studies of hedge funds is not easily exploitable, especially by large investors.